Control Of Welding Robot Using Drone With Autopilot - Anuar, Muhammad Akmal Adib (Universiti Sains Malaysia, 2019)
Drone or unmanned aerial vehicles (UAV) technology nowadays constantly evolving from day to day. This technology has widely used in many sectors such as agriculture, public services, aerial surveillance, media, delivery and others. In modern robotic industry, drone can be the best approach to replace robotic arm especially in MIG welding industry. Using drone technology, it can reduce the problem in term of limit length for welding as it doesn’t need a platform such as railways to move and perform the welding process. This can reduce the cost in building the railways and labour cost. Thus, the feasibility of combining technologies (drone and welding) in robotic welding industry and the integration of welding gun operate autonomously using relay are studied. In this research, the type of the drone use is hexa which is six propellers and this drone will fly autonomously from one point to another point using path generated in Mission Planner software. During the flight, the drone will carry the welding gun which was installed on it to perform welding process. A relay is used to trigger the welding gun to operate or not during the flight through Mission Planner. The result obtained shows that the drone cannot perform welding 1m above the ground because of the circulation of wind under the drone. Moreover, the drone cannot move to each points precisely and this affect the welding path as the resolution of GPS is big. For future work, the drone is suggested to use technology such as optitrack for non-GPS navigation as this help the drone to move from one point to another point precisely.